Organic solar cells: a study on material selection and fabrication precision - Krishnakumar, Karthika; Grover, Ashish; Kumar, Pardeep; Patra, Asit (Institute of Advanced Engineering and Science, 2025)
The accelerating development of renewable energy technologies is imperative for addressing the problems of climate change and resource depletion. Solar energy, ideal for distributed power generation and more environmentally friendly, is integral to the progression of solar technology. Organic solar cells (OSCs) have become a key innovation in this domain, offering a promising alternative to traditional solar technologies. OSCs have received a lot of interest in the preceding years owing to their capacity to increase efficiency, affordability, and longevity. However, a dearth of research and development activities aimed at improving organic photovoltaic systems exists. This work details the laborious process of building a Bulk heterojunction (BHJ) OSC, describing the manufacturing stages and subsequent device characterization. OSCs were created in this work using three active layer materials: P3HT:PCBM, PTB7:PCBM, and PCDTBT:PCBM. The comparative analysis revealed significant efficiency disparities, with PCDTBT:PCBM exhibiting superior performance and electrical properties, while challenges were encountered with aged materials, emphasizing the relevance of meticulous material handling and the use of cutting-edge fabrication machinery in achieving efficient solar cell production.